(3CjGe GdMQjI aj ejOGf GdJMQjQs - (3GdTeGY, eMeOs ((3GdbGgQIs (3TeS ddfTQ hGdJhRjYs, 2011)
(3GeVjJ KeGfjI YTQ jheG aj ejOGf GdJMQjQ CTgO eUQ GdLOjOI GdJi QSegG GdKhGQ GTgO HYjfi hCSLd GMOGKG SjcJHgG GdJGQjN HMQha ef fhQ CdeS MQGcG LOjOG hCSJWdY KhQI MbjbjI bhGegG THGH Xdeg GdhGbY hTjhN cGfhG NjQ OYes
(3GdeMJhjGJ(B: (3a(B1-(3KeGfjI YTQ jheG GSbWJ fXGe eHGQc(B--(3a(B2-(3GdNQjWI GdSjGSjI dejOGf GdJMQjQ(B--(3a(B3-(3GdTGFYGJ hGdMQH GdfaSjI(B--(3a(B4-(3GVMc GdKhQI JWdY MdhIs
7
Keywords: (3eUQs -- (3JGQjMs -- (3GdYUQ GdMOjKs; (3eUQs -- (3JGQjNs -- (3GdKhQGJs